Climate Services for Resilient Development in South Asia: Annual Report 2016-17 - Krupnik, Timothy J. (2018)
Within South Asia, efforts to develop agricultural climate services under CSRD are led by the International Maize and Wheat Improvement Center (CIMMYT). CSRD supports the agricultural climate services track described in the Investment Options Paper (IOP) for CSRD in Bangladesh, compiled by the Asian Development Bank (ADB) in 2016. CSRD’s core objectives are to prepare farmers, extension services, and agricultural policy makers with actionable climate information and crop management advisories to reduce agricultural production risks, thereby increasing the resilience of smallholder farming communities. These broad objectives are underpinned by three aligned project objectives that include (1) the development of impact-based national-scale decision tool platforms to support the Bangladesh Meteorological Department’s (BMD) agrometeorology track, (2) collaborative development and refinement of South Asian regional-scale agro-climate decision support tools, services, and products, and (3) coordination with the Asian Development Bank and other CSRD partners to boost awareness and use of climate information and services in the agricultural sector. This report summarizes CSRD activities, achievements, and challenges during the first year (from November 2016 through December 2017).